Edukasi Biopori: Cara Mengelola Sampah Di Lingkungan Rumah Warga Desa Abuan, Bangli - Putra, I Made Riyan Lesmana Adi; Haes, Putri Ekaresty (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – One location where the garbage issues remain unaddressed is Abuan Village in the Bangli Regency. The occupation produces household garbage that is improperly managed. Consequently, the goal of the community service projects in this area is to inform the residents of Abuan village about the Bipori technique. Another aims to increase the absorption of groundwater so as to minimize the potential for flooding. Moreover, the biopori method is also useful for fertilizing the soil, making it easy to plant. because there is a biological process that decomposes the waste that enters the biopori hole. Design/methodology/approach - The methods used in this community service activity include the provision of material by resource persons and direct practice which is carried out in one of the residents' houses that have been chosen by the village. Furthermore, there are three preparation method that been used uin these community service which are preparation stage, implementation stage and evaluation stage. The purpose of implementing these three stages is to be able to measure and evaluate the activities carried out. Findings – (1) There are still many people who do not know about household sorting, (2) the emergence of awareness among the people of Abuan village to manage household waste produced by sorting waste into organic and inorganic waste, (3) The community knows the stages of implementing the biopori method and after community service activities there are several people who are interested in implementing the biopori method in their home gardens. Originality/value – In order to decrease household garbage, the service team in Abuan Village is assisted by this Partnership Program in managing the waste generated by the village's houses and providing training.